2020
DOI: 10.1097/cad.0000000000000885
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering drug pitavastatin targets lung cancer and angiogenesis via suppressing prenylation-dependent Ras/Raf/MEK and PI3K/Akt/mTOR signaling

Abstract: Therapeutic agents that target both tumor cell and vascular endothelial cell may achieve additional anti-tumor efficacy, particularly in lung cancer due to the critical roles of angiogenesis during lung cancer progression and metastasis. In this work, we showed that pitavastatin, a novel cholesterol-lowering drug, potently inhibited lung cancer cells and angiogenesis. This was achieved by the induction of apoptosis and inhibition of proliferation of lung cancer cells and human lung tumor-associated endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Hu et al demonstrated that pitavastatin can inhibit LC cells and angiogenesis, which was achieved by the induction of apoptosis and inhibition of proliferation of LC cells and human lung tumor-associated endothelial cells. They also demonstrated that pitavastatin acted on LC cells and human lung tumor-associated endothelial cell by suppressing prenylation-dependent Ras/ Raf/MEK and PI3K/Akt/mTOR signaling [102].…”
Section: Antitumor Effects Of Statins In Preclinical and Clinical Studiesmentioning
confidence: 94%
“…Hu et al demonstrated that pitavastatin can inhibit LC cells and angiogenesis, which was achieved by the induction of apoptosis and inhibition of proliferation of LC cells and human lung tumor-associated endothelial cells. They also demonstrated that pitavastatin acted on LC cells and human lung tumor-associated endothelial cell by suppressing prenylation-dependent Ras/ Raf/MEK and PI3K/Akt/mTOR signaling [102].…”
Section: Antitumor Effects Of Statins In Preclinical and Clinical Studiesmentioning
confidence: 94%
“…Indeed, lower GGPP and FPP concentrations, leading to reduced RAS and Rho isoprenylation, signal transduction, and DNA synthesis, are important functional consequences of statins in the treatment of cancer [119,[158][159][160][161][162]. Inhibiting the farnesylation of these proteins restricts their activity and might hinder cancer cell proliferation [163,164]. Studies have shown that the inhibitory effect of simvastatin on the proliferation, migration and invasion of the gastric cancer cell lines MKN45 and MGC803 is due to a reduction in GGPP and RhoA activity mediated by inhibition of β-catenin and the Yes-associated protein (YAP) signaling pathways.…”
Section: Non-cholesterol-mediated Pathwaysmentioning
confidence: 99%
“…Lung cancer has the highest incidence worldwide and stands at second for its mortality rate ( Globocan, 2020 ). Non-small-cell lung carcinoma (NSCLC) shares 85% of all lung cancer and is insensitive toward cytotoxic chemotherapy ( Chen et al, 2014 ; Hu et al, 2020 ). In lung cancer, unusual overexpression or stimulation of Akt has been observed, linked with elevated cancer cell proliferation and survival ( Song et al, 2019 ).…”
Section: Cholesterol-lowering Drugs On Akt Signalingmentioning
confidence: 99%